New Year`s Eve fireworks impact on the number of magpies on the roosting place - Karolewski, Krzysztof; Bocheński, Marcin; Ciebiera, Olaf; Markulak, Damian; Jerzak, Leszek (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
Roost sites play a very important role in magpie`s life cycle. Frightening birds away may have disadvantageous influence on its population. There have been conducted researches concerning changes in roosting birds number for intense use of fireworks on New Year`s Eve.
Keywords: wróblowe; ornitologia